2021
DOI: 10.1126/scitranslmed.abg1168
|View full text |Cite
|
Sign up to set email alerts
|

Targeting acute myeloid leukemia dependency on VCP-mediated DNA repair through a selective second-generation small-molecule inhibitor

Abstract: The development and survival of cancer cells require adaptive mechanisms to stress. Such adaptations can confer intrinsic vulnerabilities, enabling the selective targeting of cancer cells. Through a pooled in vivo short hairpin RNA (shRNA) screen, we identified the adenosine triphosphatase associated with diverse cellular activities (AAA-ATPase) valosin-containing protein (VCP) as a top stress-related vulnerability in acute myeloid leukemia (AML). We established that AML was the most responsive disease to chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 73 publications
3
37
0
Order By: Relevance
“…In 2021, a second-generation CB-5083 inhibitor, CB-5339, was developed and validated in multiple AML models, such as syngeneic and patient-derived xenograft murine models. The combination of CB-5339 with a DNA-damaging agent exerted a synergistic effect on an MLL-AF9-driven AML murine model [ 143 ].…”
Section: Inhibitors Of Vcpmentioning
confidence: 99%
“…In 2021, a second-generation CB-5083 inhibitor, CB-5339, was developed and validated in multiple AML models, such as syngeneic and patient-derived xenograft murine models. The combination of CB-5339 with a DNA-damaging agent exerted a synergistic effect on an MLL-AF9-driven AML murine model [ 143 ].…”
Section: Inhibitors Of Vcpmentioning
confidence: 99%
“…Due to the essential role played by p97 in cellular processes, it is no surprise that a number of multisystem diseases are associated with mutations and dysfunctions in p97. Diseases arising from protein degradation defects ( 7 ) and DNA repair ( 8 ) such as cancer, viral infections such as the poliovirus ( 9 ), and even neurodegenerative disorders all implicate p97 as crucial in disease progression. p97 is therefore an attractive therapeutic target ( 10 ).…”
mentioning
confidence: 99%
“…Excitingly, a highly potent and selective ATP-competitive VCP inhibitor named CB-5339 is currently being evaluated in phase I clinical trials for acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) and is anticipated to enter clinical testing for solid tumors as well. Most recently, it was reported that CB-5339 is highly effective at inhibiting in vitro and in vivo growth and survival of AML cell lines and mouse xenograft models as monotherapy [64]. Interestingly, the authors also showed that CB-5339 synergizes with standard chemotherapies consisting of genotoxic anthracycline and cytarabine, supporting the general idea that VCP inhibition can be chemo-sensitizing.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, the authors also showed that CB-5339 synergizes with standard chemotherapies consisting of genotoxic anthracycline and cytarabine, supporting the general idea that VCP inhibition can be chemo-sensitizing. Not surprisingly, neither total VCP nor phospho-ATM and γH2AX levels correlate with the anticancer effects of CB-5339 [64]. Genetic profiling revealed an association between co-occurrence of RAS oncogenic activation and TP53 deficiency in AML cell lines and reduced the sensitivity to VCP inhibition.…”
Section: Discussionmentioning
confidence: 95%